Newman and the power of conviction: truth and complexity - Garnett, Jane (International journal for the study of the Christian church, 2020)
Newman returned again and again to reflect on the nature of conviction. The very process of ongoing reflection was itself fundamental: the cultivation of a contemplative cast of mind open to complexity and diversity, and resistant to relativism. Attention to such a way of thinking was the safeguard of integrity and a check on solipsistic individualism. This was crucial for the interrelationship between thought and action, and the functioning of an engaged and responsible civil society. In an increasingly pluralistic religious culture, understanding well-considered difference could strengthen faith and underpin effective action in a way that appeals to bland consensus or to a generic natural theology could never do. Whilst Newman argued for the essential consistency of principle with which he approached these questions throughout his life, projected onto his conversion was a series of cultural and political anxieties, refracted through the lens of a gendered and sexualised anti-Catholicism, of which Kingsley was a prominent exponent. However, this language was part of a much wider - and developing - contemporary discourse, involving a range of thinkers (including Maurice, Ruskin and Matthew Arnold), who deployed gender to constructive critical effect, adding to the dynamic force of diversity, which Newman harnessed. Such ways of thinking retain their pertinence in confronting questions of value in a liberal society.